Reversal of biological age in multiple rat organs by young porcine plasma fraction - Steve Horvath; Kavita Singh; Ken Raj; Shraddha I. Khairnar; Akshay Sanghavi; Agnivesh Shrivastava; Joseph A. Zoller; Caesar Z. Li; Claudia B. Herenu; Martina Canatelli-Mallat; Marianne Lehmann; Siniša Habazin; et al. (GeroScience, 2023)
Young blood plasma is known to confer beneficial effects on various organs in mice and rats. However, it was not known whether plasma from young adult pigs rejuvenates old rat tissues at the epigenetic level; whether it alters the epigenetic clock, which is a highly accurate molecular biomarker of aging. To address this question, we developed and validated six different epigenetic clocks for rat tissues that are based on DNA methylation values derived from n = 613 tissue samples. As indicated by their respective names, the rat pan-tissue clock can be applied to DNA methylation profiles from all rat tissues, while the rat brain, liver, and blood clocks apply to the corresponding tissue types. We also developed two epigenetic clocks that apply to both human and rat tissues by adding n = 1366 human tissue samples to the training data. We employed these six rat clocks to investigate the rejuvenation effects of a porcine plasma fraction treatment in different rat tissues. The treatment more than halved the epigenetic ages of blood, heart, and liver tissue. A less pronounced, but statistically significant, rejuvenation effect could be observed in the hypothalamus. The treatment was accompanied by progressive improvement in the function of these organs as ascertained through numerous biochemical/physiological biomarkers, behavioral responses encompassing cognitive functions. An immunoglobulin G (IgG) N-glycosylation pattern shift from pro- to anti-inflammatory also indicated reversal of glycan aging. Overall, this study demonstrates that a young porcine plasma-derived treatment markedly reverses aging in rats according to epigenetic clocks, IgG glycans, and other biomarkers of aging.

Epigenetic clock and methylation studies in vervet monkeys - Anna J. Jasinska; Amin Haghani; Joseph A. Zoller; Caesar Z. Li; Adriana Arneson; Jason Ernst; Kylie Kavanagh; Matthew J. Jorgensen; Julie A. Mattison; Kevin Wojta; Oi-Wa Choi; Joseph DeYoung; et al. (GeroScience, 2022)
DNA methylation-based biomarkers of aging have been developed for many mammals but not yet for the vervet monkey ( Chlorocebus sabaeus ), which is a valuable non-human primate model for biomedical studies. We generated novel DNA methylation data from vervet cerebral cortex, blood, and liver using highly conserved mammalian CpGs represented on a custom array (HorvathMammalMethylChip40). We present six DNA methylation-based estimators of age: vervet multi-tissue epigenetic clock and tissue-specific clocks for brain cortex, blood, and liver. In addition, we developed two dual species clocks (human-vervet clocks) for measuring chronological age and relative age, respectively. Relative age was defined as ratio of chronological age to maximum lifespan to address the species differences in maximum lifespan. The high accuracy of the human-vervet clocks demonstrates that epigenetic aging processes are evolutionary conserved in primates. When applying these vervet clocks to tissue samples from another primate species, rhesus macaque, we observed high age correlations but strong offsets. We characterized CpGs that correlate significantly with age in the vervet. CpG probes that gain methylation with age across tissues were located near the targets of Polycomb proteins SUZ12 and EED and genes possessing the trimethylated H3K27 mark in their promoters. The epigenetic clocks are expected to be useful for anti-aging studies in vervets.

Epigenetic clock and DNA methylation analysis of porcine models of aging and obesity - Kyle M. Schachtschneider; Lawrence B. Schook; Jennifer J. Meudt; Dhanansayan Shanmuganayagam; Joseph A. Zoller; Amin Haghani; Caesar Z. Li; Joshua Zhang; Andrew Yang; Ken Raj; Steve Horvath (GeroScience, 2021)
DNA-methylation profiles have been used successfully to develop highly accurate biomarkers of age, epigenetic clocks, for many species. Using a custom methylation array, we generated DNA methylation data from n = 238 porcine tissues including blood, bladder, frontal cortex, kidney, liver, and lung, from domestic pigs ( Sus scrofa domesticus ) and minipigs (Wisconsin Miniature Swine™). Samples used in this study originated from Large White X Landrace crossbred pigs, Large White X Minnesota minipig crossbred pigs, and Wisconsin Miniature Swine™. We present 4 epigenetic clocks for pigs that are distinguished by their compatibility with tissue type (pan-tissue and blood clock) and species (pig and human). Two dual-species human-pig pan-tissue clocks accurately measure chronological age and relative age, respectively. We also characterized CpGs that differ between minipigs and domestic pigs. Strikingly, several genes implicated by our epigenetic studies of minipig status overlap with genes (ADCY3, TFAP2B, SKOR1, and GPR61) implicated by genetic studies of body mass index in humans. In addition, CpGs with different levels of methylation between the two pig breeds were identified proximal to genes involved in blood LDL levels and cholesterol synthesis, of particular interest given the minipig’s increased susceptibility to cardiovascular disease compared to domestic pigs. Thus, breed-specific differences of domestic and minipigs may potentially help to identify biological mechanisms underlying weight gain and aging-associated diseases. Our porcine clocks are expected to be useful for elucidating the role of epigenetics in aging and obesity, and the testing of anti-aging interventions.

Multi-Tissue Methylation Clocks for Age and Sex Estimation in the Common Bottlenose Dolphin - Todd R. Robeck; Zhe Fei; Amin Haghani; Joseph A. Zoller; Caesar Z. Li; Karen J. Steinman; Stacy Dirocco; Lydia Staggs; Todd Schmitt; Steve Osborn; Gisele Montano; Magdalena Rodriguez; et al. (Frontiers in Marine Science, 2021)
Accurate identification of individual ages within wild bottlenose dolphins ( Tursiops truncatus ) is critical for determining population health and the development of population management strategies. As such, we analyzed DNA methylation (DNAm) patterns by applying a custom methylation array (HorvathMammalMethyl40) to both blood ( n = 140) and skin samples ( n = 87) from known age or approximate age (0–57 years) bottlenose dolphins. We present three bottlenose dolphin specific age estimation clocks using combined blood and skin [48 CpGs, R = 0.93, median absolute error (MAE) = 2.13 years], blood only (64 CpGs, R = 0.97, error = 1.46 years) and skin only (39 CpGs, R = 0.95, error = 2.53). We characterized individual cytosines that correlate with sex and age in dolphins and developed a sex estimator based on 71 CpGs that predicts the sex of any odontocete species with 99.5% accuracy. The presented epigenetic clocks are expected to be useful for conservation efforts and for determining if anthropogenic events affect aging rates in wild populations.

What are the implications of sea-level rise for a 1.5, 2 and 3 °C rise in global mean temperatures in the Ganges-Brahmaputra-Meghna and other vulnerable deltas? - Sally Brown; Robert J. Nicholls; Attila N. Lázár; Duncan D. Hornby; Chris Hill; Sugata Hazra; Kwasi Appeaning Addo; Anisul Haque; John Caesar; Emma L. Tompkins (Regional Environmental Change, 2018)

North Atlantic observations sharpen meridional overturning projections - R. Olson; S.-I. An; Y. Fan; J. P. Evans; L. Caesar (Climate Dynamics, 2018)

West Africa climate extremes and climate change indices - A. A. Barry; J. Caesar; A. M. G. Klein Tank; E. Aguilar; Carol McSweeney; Ahmed M. Cyrille; M. P. Nikiema; K. B. Narcisse; F. Sima; G. Stafford; L. M. Touray; J. A. Ayilari‐Naa; et al. (International Journal of Climatology, 2018)
Observational analyses of changing climate extremes over the West Africa region have been limited by the availability of long and high‐quality datasets. To help address this gap, a climate extremes indices workshop was held in the Gambia in December 2011 with participants from 14 West African countries. The resulting analysis utilized 15 annual indices derived from observed daily temperatures and 10 annual indices derived from observed daily precipitation. The analysis was conducted for 166 meteorological stations in 13 countries for 2 periods: 1960–2010 and 1981–2010. The analyses of trends in the annual mean temperature indices have identified statistically significant increases of 0.16 °C/decade and 0.28 °C/decade for mean annual maximum and mean annual minimum temperatures, respectively, averaged over all available land stations in the region during the last 50 years. The seasonal‐temperature‐related indices show significant patterns of warming in all seasons. The annual mean of daily minimum temperature has increased more than the annual mean of daily maximum temperature leading to a decreasing trend in the diurnal temperature range. Warm days and warm nights have become more frequent, and cold days and cold nights have become less frequent. The analyses of precipitation‐based indices indicate spatially non‐coherent changes throughout the study area with few statistically significant trends over the longer period. Exceptions to this are the simple daily intensity index and maximum 5‐day precipitation, which show significant increasing regional trends over both the shorter and longer periods. Additionally, over the recent period (1981–2010) most of the precipitation related indices show significant trends towards wetter conditions. However, this period of increased rainfall follows a decade of significantly drier conditions in the region – it is not clear whether the recent upward trends reflect the ‘recovery’ from this long drought period or represents a long‐term response to warming.

Changes in temperature and precipitation extremes over the Indo‐Pacific region from 1971 to 2005 - J. Caesar; L. V. Alexander; B. Trewin; K. Tse‐ring; L. Sorany; V. Vuniyayawa; N. Keosavang; A. Shimana; M. M. Htay; J. Karmacharya; D. A. Jayasinghearachchi; J. Sakkamart; et al. (International Journal of Climatology, 2011)
Up‐to‐date regional and local assessments of changing climate extremes are important to allow countries to make informed decisions on mitigation and adaptation strategies, and to put these changes into a global context. A workshop for countries from the Indo‐Pacific region has brought together daily observations from 13 countries for an analysis of climate extremes between 1971 and 2005. This paper makes use of the workshop outcomes and post‐workshop analyses to build on previous work in Southeast Asia to update the assessment of changing climate extremes using newly available station data. We utilise a consistent and widely tested methodology to allow a direct comparison of the results with those from other parts of the world. The relationship of inter‐annual variability in the climate extremes indices with sea surface temperature (SST) patterns has been investigated with a focus on the influence of the El Niño‐Southern Oscillation phenomenon. The results support findings from elsewhere around the globe that warm extremes, particularly at night, are increasing and cold extremes are decreasing. Trends in precipitation extremes are less spatially consistent across the region. © Royal Meteorological Society and Crown Copyright 2010.